Community and sustainable water resource mangement : a case study of Ban Limthong, Amphoe Nang Rong, Changwat Buri Ram - Royboon Rassameethes (Chulalongkorn University, 2012)
Thesis (Ph.D.)--Chulalongkorn University, 2009